Transitverkehr am Oberrhein. - Speck, Georg (Deutscher Verkehrs-Verl., 2006)
Der Aufsatz beruht auf einem Bericht, den der Verfasser als Leiter der Arbeitsgruppe Verkehrspolitik der deutsch-französisch-schweizerischen Oberrheinkonferenz (ORK), einer grenzüberschreitenden Behördenkooperation der Regionen am Oberrhein, im Dezember 2004 dem Plenum der ORK vorgelegt und den diese zustimmend zur Kenntnis genommen hat. Nach weiterführenden Diskussionen, u. a. mit Vertretern der Wirtschaft, und entsprechender Anpassung soll er nun in das geplante verkehrspolitische Leitbild der ORK einfließen. difu

The Upper Rhine Region is confronted with the challenge of coping with the ongoing increase in North-South transit traffic. Residents are no longer inclined to sacrifice more of their quality of life and put up with damage to their environment. The ORK, a regional German-French-Swiss Upper Rhine cooperative council, seeks to coordinate national plans, especially with regard to investments in transport, in order to improve transporters' performance and to minimize any negative impact on the population. The article is based on a multimodal traffic evaluation study comissioned by the ORK, plus additional research. It presents an overview of problems related to rail an road transport, and offers recommendations for their solution. difu
Keywords: Verkehr; Verkehrsplanung; Verkehrsinfrastruktur; Verkehrspolitik; Kooperation; Behörde; Straßenverkehr; Schienenverkehr; Güterverkehr; Personenverkehr; Wasserverkehr; Transitverkehr; Grenzüberschreitender Verkehr; Infrastrukturkosten; Verkehrsverwaltung; Verwaltungszusammenarbeit; Transitverkehr; Verkehrsträger